Practical use of non-steroidal anti-inflammatory drugs in farm practice. (2nd September 2020) - Reader, Jon; Angel, Tom; Rogers, Imogen
Abstract : The importance of pain relief in farm animals has never been further up the agenda for modern food production and farm animal practice. This has been driven by increased awareness amongst farmers, veterinary surgeons and consumers. This article looks at the practical use of non-steroidal anti-inflammatory drugs (NSAIDs) in farm animal practice for both adults and youngstock. The basic mode of action of NSAIDs is discussed and some of the evidence base that has been growing over the use of NSAIDs in cattle. It also highlights some of the present requirements of some of the retailers and auditing bodies.